DISCOURSE OF WASIAT WAJIBAH IN REVIEW OF ISTINBATH ISLAMIC LAW - Watni Marpaung; Muhammad Amar Adly (Universitas Islam Negeri Sumatera Utara, 2022)
This paper will explain the concept of wasiat wajibah will in review of istinbath Islamic law. The presence of the wasiat wajibah will which is one of the characteristics of Indonesian Islamic law contained in the Compilation of Islamic Law (KHI) is important. Tracing on classical fiqh and Islamic law istinbat methods is a way to legally place a wasiat wajibah will